Respuesta :

Explanation:

Here we have the following function:

[tex]f(x)=\sqrt{9-x}+\frac{-2x+1}{x+2}[/tex]

By property:

[tex]\left(f\pm g\right)'=f\:'\pm g'[/tex]

Then:

[tex]\frac{df}{dx}=\frac{d}{dx}\left(\sqrt{9-x}\right)+\frac{d}{dx}\left(\frac{1-2x}{x+2}\right)[/tex]

From here:

[tex]\frac{d}{dx}\left(\sqrt{9-x}\right)=-\frac{1}{2\sqrt{9-x}}[/tex]

And:

[tex]\frac{d}{dx}\left(\frac{1-2x}{x+2}\right)=\frac{\frac{d}{dx}[\left(1-2x\right)]\left(x+2\right)-\frac{d}{dx}[\left(x+2\right)]\left(1-2x\right)}{\left(x+2\right)^2} \\ \\ =\frac{\left(-2\right)\left(x+2\right)-1\cdot \left(1-2x\right)}{\left(x+2\right)^2}= -\frac{5}{\left(x+2\right)^2}[/tex]

Therefore:

[tex]\boxed{\frac{df}{dx}=-\frac{1}{2\sqrt{9-x}}-\frac{5}{\left(x+2\right)^2}}[/tex]

ACCESS MORE